Solve for z 3z-4+2z=6+2z-4

Math
3z-4+2z=6+2z-4
Add 3z and 2z.
5z-4=6+2z-4
Subtract 4 from 6.
5z-4=2z+2
Move all terms containing z to the left side of the equation.
Tap for more steps…
Subtract 2z from both sides of the equation.
5z-4-2z=2
Subtract 2z from 5z.
3z-4=2
3z-4=2
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Add 4 to both sides of the equation.
3z=2+4
Add 2 and 4.
3z=6
3z=6
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3z=6 by 3.
3z3=63
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3z3=63
Divide z by 1.
z=63
z=63
Divide 6 by 3.
z=2
z=2
Solve for z 3z-4+2z=6+2z-4

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top